Epidemiology of healthcare-associated infection reported from a hospital-wide incidence study: considerations for infection prevention and control planning. (August 2021) - Stewart, S.; Robertson, C.; Pan, J.; Kennedy, S.; Dancer, S.; Haahr, L.; Manoukian, S.; Mason, H.; Kavanagh, K.; Cook, B.; Reilly, J.
Summary: Background: The measure of disease frequency most widely used to report healthcare-associated infection (HAI) is the point-prevalence survey. Incidence studies are rarely performed due to time and cost constraints; they show which patients are affected by HAI, when and where, and inform planning and design of infection prevention and control (IPC) measures. Aim: To determine the epidemiology of HAI within a general and a teaching hospital in Scotland. Methods: A prospective observational incidence study was undertaken for one year from April 2018 using data collected as part of the Evaluation of Cost of Nosocomial Infection (ECONI) study. A novel, robust approach was undertaken, using record linkage to national administrative data to provide full admission and discharge information. Cases were recorded if they met international HAI definitions. Findings: Incidence of HAI for the combined hospitals was 250 HAI cases per 100, 000 acute occupied bed-days (AOBD). Highest frequency was in urinary tract (51.2 per 100, 000 AOBD), bloodstream (44.7), and lower respiratory tract infection (42.2). The most frequently reported organisms were Escherichia coli, Staphylococcus aureus, and norovirus. Incidence of HAI was higher in older people and emergency cases. There was an increase in the rate of HAI in summer months (pneumonia, respiratory, surgical, and gastrointestinal infection) and in winter months norovirus gastrointestinal infection ( P < 0.0001). The highest incidence specialties were intensive care, renal medicine, and cardiothoracic surgery. HAI occurred at a median of 9 days (interquartile range: 4–19) after admission. Incidence data were extrapolated to provide an annual national estimate of HAI in NHS Scotland of 7437 (95% confidence interval: 7021–7849) cases. Conclusion: This study provides a unique overview of incidence of HAI and identifies the burden of HAI at the national level for the first time. Understanding the incidence in different clinical settings, at different times, will allow targeting of IPC measures to those patients who would benefit the most.